Faktor-Faktor yang Mempengaruhi Pengetahuan Remaja tentang Kesehatan Reproduksi di Kelas XI SMAN 2 Karawang - Putri, Shilvi Septiani; Anggraini, Nofa (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT In Indonesia, knowledge regarding reproductive health is still relatively low. With adequate knowledge, teenagers will find it difficult to avoid risky sexual attitudes due to a lack of information that can change their views and behavior about things that endanger their reproductive health and future health. Based on an initial survey that carried out interviews with 10 students, the results were that 7 out of 10 students had insufficient knowledge about reproductive health and did not get enough information related to sexuality and HIV/AIDS from school, home and social media. To determine the factors that influence adolescents' knowledge about reproductive health.The research.  The research method used was cross-sectional. The sample for this research was 80 students of SMAN 2 Karawang. The sampling technique is Proportional stratified random sampling. Technical data analysis uses univariate analysis and bivariate analysis using the chi-square test (X2) SPSS version 26 program. Knowledge from teenagers, as many as 28 respondents (35%) had negative beliefs/culture, as many as 28 respondents (35%) had less information from parents, as many as 25 respondents (31.3%) had less information from the media. There is no relationship between belief/culture and teenagers' knowledge about reproductive health at SMAN 2 Karawang (p-value = 0.958), there is a relationship between parental information and information from the media and teenagers' knowledge about reproductive health at SMAN 2 Karawang (p-value = 0.032). That information from parents and information from the media are factors that have a significant influence on knowledge about reproductive health in adolescents. The educational community, society and parents should pay more attention to support and education regarding reproductive health information and knowledge for children as early as possible. Keywords: Factors, Knowledge, Adolescents, Reproductive Health  ABSTRAK Di Indonesia pengetahuan terkait kesehatan reproduksi masih terbilang rendah. Dengan pengetahuan yang memadai, remaja akan susah menghindari sikap seksual berisiko karena kurangnya informasi yang bisa mengubah pandangan dan perilakunya tentang hal-hal yang membahayakan kesehatan reproduksi dan kesehatan masa depannya. Berdasarkan survey awal yang dilaksanakannya wawancara dengan 10 orang siswa/siswi, Maka didapatkannya hasil bahwa 7 dari 10 orang siswa/siswi memiliki pengetahuan kurang tentang kesehatan reproduksi dan kurang mendapatkannya informasi terkait seksualitas dan HIV/AIDS dari sekolah, rumah dan sosial media. Mengetahui faktor-faktor yang mempengaruhi pengetahuan remaja tentang kesehatan reproduksi. Metode penelitian yang digunakan adalah cross-sectional. Sampel penelitian ini adalah siswa/i kelas XI SMAN 2 Karawang sebanyak 391 responden. Teknik pengambilan sampel yaitu Proportional stratified random sampling sebanyak 80 responden. Teknis analisa data menggunakan analisis univariat dan analisis bivariat menggunakan uji chi-square (X2) program SPSS versi 26. Diketahui dari pengetahuan remaja, sebanyak 28 responden (35%) kepercayaan/budaya  yang negatif, sebanyak 28 responden (35%) informasi dari orang tua yang kurang, sebanyak 25 responden (31,3%) informasi dari media yang kurang. Tidak ada hubungan antara kepercayaan/budaya dengan pengetahuan remaja tentang kesehatan reproduksi di SMAN 2 Karawang (p-value = 0,958), ada hubungan antara informasi dari orang tua dan informasi dari media dengan pengetahuan remaja tentang kesehatan reproduksi di SMAN 2 Karawang (p-value = 0,032). Informasi dari orang tua dan informasi dari media merupakan faktor yang berpengaruh signifikan terhadap pengetahuan tentang kesehatan reproduksi pada remaja. Civitas pendidikan, Masyarakat, dan para orang tua agar lebih memperhatikan dukungan dan edukasi terhadap informasi dan pengetahuan kesehatan reproduksi pada anak sedini mungkin. Kata Kunci : Faktor-Faktor, Pengetahuan, Remaja, Kesehatan Reproduksi